Arsenic and heavy metal concentrations in agricultural soils in South Savo province - Mäntylahti, Väinö; Laakso, Pirkko (MTT Agrifood Research Finland, 2002)
Syksyllä 2000 kerättiin Etelä-Savosta Maaseutukeskus Mikkelin alueelta 23 tilalta 274 näytettä kivennäismaista ja 38 näytettä eloperäisistä maista. Näytteet otettiin tavanomaisilta viljelysmailta, ja niistä määritettiin kuningasveteen uuttuvien arseenin, kromin, kadmiumin, kuparin, elohopean, nikkelin, lyijyn ja sinkin pitoisuudet. Alkuainepitoisuudet laskettiin perinteisesti yksikköinä mg/kg, mutta myös yksikköinä mg/l, koska maan irtotiheyden oletettiin vaikuttavan tuloksiin. Alkuainepitoisuuksien mediaanit olivat:As 2,90 mg/kg, Cd 0,084 mg/kg, Cr 17,0 mg/kg, Cu 13,0 mg/kg, Hg 0,060 mg/kg, Ni 5,4 mg/kg, Pb 7,7 mg/kg, Zn 36,5 mg/kg. Eloperäisillä mailla vastaavat tulokset olivat:As 2,80 mg/kg, Cd 0,265 mg/kg, Cr 15,0 mg/kg, Cu 29,0 mg/kg, Hg 0,200 mg/kg, Ni 5,9 mg/kg, Pb 11,0 mg/kg, Zn 25,5 mg/kg. Kivennäismaiden ja eloperäisten maiden kadmium- ja elohopeapitoisuudet poikkesivat toisistaan. Muutamat arseenin, kadmiumin ja elohopean pitoisuudet ylittivät ns. taustaarvot, mutta eivät saastuneiden maiden raja-arvoja. Useimmissa Etelä-Savon pelloissa oli vain pieniä määriä arseenia ja raskasmetalleja, kun pitoisuuksia verrattiin Suomen, muiden Pohjoismaiden ja Keski-Euroopan viljelysmaihin. Näitä Etelä-Savon peltoja voitaisiin käyttää erikoisviljelyyn varustaen ne Puhdas maa -merkinnällä.

Increasing concentrations of arsenic and heavy metals in agricultural soils are becoming a growing problem in industrialized countries. These harmful elements represent the basis of a range of problems in the food chain, and are a potential hazard for animal and human health. It is therefore important to gauge their absolute and relative concentrations in soils that are used for crop production. In this study the arsenic and heavy metal concentrations in 274 mineral soil samples and 38 organogenic soil samples taken from South Savo province in 2000 were determined using the aqua regia extraction technique. The soil samples were collected from 23 farms.The elements analyzed were arsenic, cadmium, chromium, copper, mercury, nickel, lead and zinc. The median concentrations in the mineral soils were:As 2.90 mg kg 1, Cd 0.084 mg kg 1, Cr 17.0 mg kg 1, Cu 13.0 mg kg 1, Hg 0.060 mg kg 1, Ni 5.4 mg kg 1, Pb 7.7 mg kg 1, Zn 36.5 mg kg 1. The corresponding values in the organogenic soils were:As 2.80 mg kg 1, Cd 0.265 mg kg 1, Cr 15.0 mg kg 1, Cu 29.0 mg kg 1, Hg 0.200 mg kg 1, Ni 5.9 mg kg 1, Pb 11.0 mg kg 1, Zn 25.5 mg kg 1. The results indicated that cadmium and mercury concentrations in the mineral and organogenic soils differed. Some of the arsenic, cadmium and mercury concentrations exceeded the normative values but did not exceed limit values. Most of the agricultural fields in South Savo province contained only small amounts of arsenic and heavy metals and could be classified as Clean Soil . A draft for the target values of arsenic and heavy metal concentrations in Clean Soil is presented.
Keywords: ys; Etelä-Savo; Suomi; viljelymaa; maaperä; arseeni; raskasmetallit; arsenic; heavy metals; soil; classification; normative and limit values; soil pollution; Finland